Prevention, Health Promotion and Personal Bioethics in the defense and promotion of human life - Morán Huanay, Carla Elisa (2020)
This paper aims to reflect on the theme of Prevention, Health Promotion and Personal Bioethics in the defense and promotion of human life. Today more than ever it is necessary to maintain a vigilant look at human life, which is continually exposed to dangers that affect the health and well-being of people, hence the need for an incisive health promotion that benefits everyone. Personalistic Bioethics in this context is proposed through three of its principles as the model that defends the human person and its dignity, in the promotion of health care and the life of each person, as both an individual and a collective commitment.